PENGARUH LAJU AIR UMPAN DAN UDARA PADA GASIFIKASI FLUIDIZED BED LIMBAH KAYU KAMPER (DRYOBALANOPS SPP) - Tjutju Nurhayati; Hartoyo Hartoyo (Jurnal Penelitian Hasil Hutan, 1992)
This research studied  the  fluizided bed gasification  process of wood  waste that could produce  highly yield  and good quality   of fuel gas.The processing  treatments  were conducted at 3 levels of  wood  feed flow  rate i.e 3. 6., 3.8 and 4.2  kgs/hour and 5 leveis  of air flow rate i.e  4.4,  4.7, 5.0,5.4 and 6.5  m3/hour.The  result  revaled that highest  caloriffic  value of produced gas was 7.106  MJ/m3   which  resulted  from  wood  feed and air  flow  rate  3. 6 kg/hour  and  4. 4  m3 /hour, respectively.  The product   gas composition  of  this  rate  was H2  = 5. 62 .CH = 3.99; CO=  11.77; C2H4 = 4.34;  C2H6 = 0.21; N2 = 57.69; 02 = 0.40 and C02 = 15. 71 (in  %  volume)The highest  total  energy  of product   gas was 20.36  MJ/m3  with fuel gas efficiency 26.16% which  resulted  from  feed and  air flow rote  4.2 kg/hour  and  6.5  m3/hour, respectively.  The product   gas composition at this rate  was H2  = 6.03; CH4  = 3.51;  CO=  12.60;  C2H4  = 2.46; C2H6  = 0.16; N2  = 57.23;  02  = 0.45  and C02   = 17.58,  while  the fluidued   bed gasification process  was held at 97oᵒC.